Cavitation performance improvement of engine cooling pump - Karbal, Doğukan (Graduate School, 2025)
As part of this study, the cavitation issue observed at the specific operating point of the water pump used in the cooling system of an off-road vehicle was investigated, and an optimization process was conducted to address the problem. The optimization process consisted of three stages. In the first stage, based on the insights gained from a literature review, different designs for the impeller's blade leading-edge profile were tested. The impact of three different blade leading edge configurations (v0, v1, and v2) on the impeller's cavitation performance was investigated using 3D CFD analysis. The initial analyses were performed in steady-state conditions using ANSYS CFX. Regions on the impeller with pressures below the vapor pressure of the fluid were compared, and the optimal design (v2) was selected. Following the selection of the optimal design, cavitation analyses were conducted on the pump model with the baseline impeller and the pump model with the optimized impeller using ANSYS CFX. These analyses employed the Rayleigh-Plesset cavitation model and were solved under time-dependent conditions. The results demonstrated that the optimized design exhibited superior cavitation performance compared to the baseline design. The optimized impeller was then manufactured and subjected to experimental cavitation tests. These tests revealed that the optimized impeller allowed the pump to operate at 30% lower inlet pressure before cavitation occurred compared to the baseline pump, confirming the significant effectiveness of the optimization process. Subsequently, the final impeller design underwent experimental performance testing, and a validation study was carried out by comparing the experimental results with 3D CFD results. The validation analyses were performed using Siemens StarCCM+ in time-dependent conditions. The comparison between 3D CFD results and experimental data showed a maximum deviation of 3%, confirming the validity of the numerical approach. Performance test results were compared both numerically and experimentally using H-Q curves, which are presented for clarity.
Motor soğutma pompasının kavitasyon performansının iyileştirmesi
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2025
Keywords: engine cooling pump; motor soğutma pompası; cooling; soğutma